2019
DOI: 10.1038/s41598-019-41142-z
|View full text |Cite|
|
Sign up to set email alerts
|

Simple Tyrosine Derivatives Act as Low Molecular Weight Organogelators

Abstract: The gelation of L-Tyr(tBu)-OH in tetrahydrofuran (THF) was discovered serendipitously. It was noted that this tremendously low molecular weight (LMW) compound has the ability to gel a wide variety of organic solvents (e.g., N,N-Dimetylformamide (DMF), THF, butanol, toluene), even in very low concentrations (i.e., 0.1 wt/v% in DMF). Addition of bases such as NaOH and piperidine enhanced the gel property. By changing the side-chain protecting group to tert-butyldimethylsilyl (TBDMS), a fluoride ion-responsive or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…situ, 15 and enzyme-mediated chemical changes can trigger selfassembly. [16][17][18] Catalysis plays an intimate role in controlling nonequilibrium fuelled systems in both assembly/disassembly pathways.…”
mentioning
confidence: 99%
“…situ, 15 and enzyme-mediated chemical changes can trigger selfassembly. [16][17][18] Catalysis plays an intimate role in controlling nonequilibrium fuelled systems in both assembly/disassembly pathways.…”
mentioning
confidence: 99%
“…The analysis outcomes made this molecule more special as the gelation could be carried out in all classes of solvents; be it polar, protic, apolar, etc. The gelation in sunflower oil and diesel makes it an appropriate candidate for drug delivery (Aykent et al, 2019). Further investigations revealed the same capability of other enantiomer, H-D-Tyr(tBu)-OH to form the organogel while racemic H-DL-Tyr(tBu)-OH was unsuccessful to do so.…”
Section: Single or Modified Single Amino Acidsmentioning
confidence: 94%
“…Further investigations revealed the same capability of other enantiomer, H-D-Tyr(tBu)-OH to form the organogel while racemic H-DL-Tyr(tBu)-OH was unsuccessful to do so. The new work also exposed the role of tert-butyl moiety as H-Tyr-OH, H-Phe-OH and H-Tyr(Me)-OH could not form gel while H-Tyr(tBu)-OH could do so as mentioned above (Aykent et al, 2019).…”
Section: Single or Modified Single Amino Acidsmentioning
confidence: 96%
“…Apparently, based on the number of known examples, one of the most frequent N-derivatization is the amide generation, but no other, such as the obtaining of a secondary amine group. So far, Tyr does not give rise to hydrogels like Phe, and on the other hand, there are just a few examples of supramolecular gels constructed by Tyr-based building blocks . Inspired by the remarkable self-assembly properties of these two amino acids and having in mind the possibility to modify and expand their supramolecular and physical properties through derivatization, we synthesized new molecules using the aldehyde piperonal, named as Phepip and Tyrpip (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, Tyr does not give rise to hydrogels like Phe, and on the other hand, there are just a few examples of supramolecular gels constructed by Tyrbased building blocks. 42 Inspired by the remarkable selfassembly properties of these two amino acids and having in mind the possibility to modify and expand their supramolecular and physical properties through derivatization, we synthesized new molecules using the aldehyde piperonal, named as Phepip and Tyrpip (Figure 1). We recently tested their use as ligands for the construction of Ni(II) coordination complexes, and it was demonstrated that the nuclearity and properties of the resulting systems were related to the selfassembly, where the presence or absence of the phenolic OH was critical.…”
Section: ■ Introductionmentioning
confidence: 99%